Early attempts at closer relations between Natal and the Cape Colony. 1850-1879 (Historia, 2021)
Historians of the British Empire have given considerable attention to the relations between the Mother Country and her colonial offspring, but very little to inter-colonial relations. One consequence of this neglect has been to credit with an undeserved originality the proposals made by Imperial statesmen and officials in the third quarter of the nineteenth century for the creation of closer ties between the South Mrican states. It was the sponsorship rather than the novelty of the 'schemes of Sir George Grey and Lord Carnarvon that was significant. The tragedy of South African history derives in no small measure from the very failure of an almost uninterrupted series of locally-inspired attempts at closer relations between two or more of the states in the second half of the nineteenth century. Detailed study has, in recent decades, been made of the halting attempts of the Boer republics of the hinterland to take a united stand against the dangers which threatened to overwhelm them, and of the even greater hesitation with which the Cape Colony regarded any proposals for closer union with one or both of those northern neighbours.l But no account has yet been taken of the successive failures to link the two coastal British colonies, Natal and the Cape. That unsuccessfu{ efforts were made from the earliest days from within those colonies themselves boded ill for the far bolder and more comprehensive plans of Lord Carnarvon in the eighteen-seventies
Keywords: Natal; Inter-colonial relations; Cape Colony; Lord Carnarvon